Nutrient (N, P, K) use efficiency and nitrogen balance in a bioenergy plantation of Populus deltoides clone Lux in San Piero A Grado (Pisa), Italy - Cabrera Ariza, Antonio María; Ragaglini, Giorgio; Silva Flores, Patricia; Bustos Letelier, Óscar; Santelices Moya, Rómulo (BOSQUE, 2021)
Energy crops have proved to be a viable alternative to fossil fuels. However, high biomass production always means that large quantities of nutrients from the soil are removed at harvest. The goal of this work was to estimate nutrient (nitrogen, phosphorous, potassium) use efficiency (NUE) and nitrogen balance in an eight-year-old Populus deltoides clone Lux, short rotation forestry under two cutting cycles, every two (biennial) and three (triennial) years, carried out under Mediterranean climate conditions. Results indicate that NUE, for all the analyzed elements, contained variations with slightly higher values for nitrogen and phosphorous in the triennial cycle. Although poplar cultivation has a positive nutrient efficiency, in terms of nitrogen, there is significant loss of this element in the crop cycle.